New Recorded of Metallo-β-Lactamase (blaGIM) Genes Among Klebsiella pneumoniae Clinical Isolates in Al-Najaf, Iraq - Alqaws, Hanan Mohammed; Al-Muhanna , Abbas Shakir (Medical Science Journal for Advance Research, 2026)
Background: Klebsiella pneumoniae is significant pathogen causing nosocomial and community opportunistic infections. It has become a challenge because many strains are resistant to all β-lactam antibiotics through the production of carbapenemases. Objectives: The study aims to detect the presence of blaGIM, blaVIM, and blaNDM genes encoding metallo-β-lactamases (MBL) in K. pneumoniae isolates using polymerase chain reaction (PCR) analysis. Methodology: A total of 120 clinical samples were collected, among which 100(83.33%) specimens exhibited bacterial growth of the cases. Thirty-seven (37%) isolates were identified as Klebsiella pneumoniae, and antimicrobial susceptibility testing was conducted using the Vitek-2 system. Phenotypic detection of metallo-β-lactamase (MBL) production was performed using modified carbapenem inactivation method (mCIM). Furthermore, PCR analysis was employed to detect the presence of blaGIM, blaVIM, and blaNDM genes encoding MBL in the K. pneumoniae isolates. Results: Among the 37 K. pneumoniae isolates, a high level of resistance to multiple antibiotics was observed. (97.3%) of isolates were resistance to ceftriaxone, cefixime, ciprofloxacin, and levofloxacin, (94.6%) for ceftazidime, (81.08%) for trimethoprim /sulfamethoxazole, (89.19%) for tobramycin, (86.5%) for cefepime and gentamicin, (81.08%) for piperacillin /tazobactam, (78.4%) for amikacin, (75.7%) for ertapenem, (72.9%) for minocycline, (70.27%) for meropenem and imipenem Phenotypic detection of MBL using mCIM identified 27(72.97%) isolates as MBL producers. PCR results showed that7(19%) of isolates carried the blaGIM while 19(51.4%) contained the blaVIM gene and (36)97.3% carried the blaNDM gene. Conclusions: The significant increase in multidrug-resistant (MDR) K. pneumoniae and high resistance to most antibiotics was due to the predominance of non-traditional resistance genes, such as blaGIM blaVIM, in the local environment.